Cognitive and linguistic abilities and perceptual restoration of missing speech: Evidence from online assessment - Burleson, Andrew M.; Souza, Pamela E. (Frontiers in Psychology, 2022)
When speech is clear, speech understanding is a relatively simple and automatic process. However, when the acoustic signal is degraded, top-down cognitive and linguistic abilities, such as working memory capacity, lexical knowledge (i.e., vocabulary), inhibitory control, and processing speed can often support speech understanding. This study examined whether listeners aged 22-63 (mean age 42 years) with better cognitive and linguistic abilities would be better able to perceptually restore missing speech information than those with poorer scores. Additionally, the role of context and everyday speech was investigated using high-context, low-context, and realistic speech corpi to explore these effects. Sixty-three adult participants with self-reported normal hearing completed a short cognitive and linguistic battery before listening to sentences interrupted by silent gaps or noise bursts. Results indicated that working memory was the most reliable predictor of perceptual restoration ability, followed by lexical knowledge, and inhibitory control and processing speed. Generally, silent gap conditions were related to and predicted by a broader range of cognitive abilities whereas noise burst conditions were related to working memory capacity and inhibitory control. These findings suggest that higher-order cognitive and linguistic abilities facilitate the top-down restoration of missing speech information and contribute to individual variability in perceptual restoration.